Exploring the experiences of counsellors working with boarders in UK independent schools: an Interpretative Phenomenological Analysis. - Sherborne, Harriet (2017)
An increasing evidence base describes how people working with trauma survivors may experience vicarious posttraumatic growth (VPTG). In this qualitative study, the experiences were explored of six counsellors working with current boarders in UK independent schools, and their experiences of personal change were considered through the lens of VPTG. Semi-structured interviews were conducted and Interpretative Phenomenological Analysis was used. Three themes emerged from the data: outside/inside; culture and expectations; parent+child. All six participants experienced growth corresponding with vicarious exposure to trauma. Implications for the theory of VPTG are discussed, and suggestions are made for the training and support of staff working with boarders, and for the care of boarders themselves.